1994
DOI: 10.1046/j.1471-4159.1994.63051855.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol‐Induced Oxygen Radical Formation and Lipid Peroxidation in Rat Brain: Effect of Chronic Alcohol Consumption

Abstract: The effect of chronic and in vitro ethanol exposure on brain oxygen radical formation and lipid peroxidation was analyzed . Ethanol induces a dose-dependent increase in lipid peroxidation in brain homogenates. The peroxidative effects of alcohol seem to be related to both cytochrome P450 and the ethanol-inducible form of cytochrome P450 (CYP2E1), because preincubation with metyrapone (an inhibitor of cytochrome P450) or with an antibody against CYP2E1 abolished the ethanol-increased lipid peroxidation . Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
127
0
5

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(137 citation statements)
references
References 35 publications
5
127
0
5
Order By: Relevance
“…Acute ethanol treatment results in an increased lipid peroxide level and a decreased glutathione level in rat brain homogenates (Uysal et al 1989). Both in vitro ethanol addition and chronic alcohol consumption have been demonstrated to lead to the enhanced formation of ROS and increased lipid peroxidation in the rat brain (Montoliu et al 1994). Higher levels of lipid peroxidation in different brain regions and also in the liver were measured after both acute and chronic ethanol administrations in rats (Calabrese et al 1996;Calabrese et al 1998).…”
Section: The Effects Of Alcohol On Cellular Physiologymentioning
confidence: 99%
“…Acute ethanol treatment results in an increased lipid peroxide level and a decreased glutathione level in rat brain homogenates (Uysal et al 1989). Both in vitro ethanol addition and chronic alcohol consumption have been demonstrated to lead to the enhanced formation of ROS and increased lipid peroxidation in the rat brain (Montoliu et al 1994). Higher levels of lipid peroxidation in different brain regions and also in the liver were measured after both acute and chronic ethanol administrations in rats (Calabrese et al 1996;Calabrese et al 1998).…”
Section: The Effects Of Alcohol On Cellular Physiologymentioning
confidence: 99%
“…Human body has an oxidative stress defense system, which is both enzymatic (superoxide dismutase, catalase, and glutathione peroxidase) and non-enzymatic (glutathione, thiol, tocopherols, etc.) (31). The nervous tissue is more sensitive to oxidative stress than other tissues because of its low antioxidant activity (32).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, excessive ethanol consumption increased the MDA levels of rat brain synaptosomes (9). Montoliu et al (31) showed that ethanol augments reactive oxygen species and lipid peroxidation in synaptosomes. Also, in another study, chronic ethanol consumption increased the MDA levels of rat brain synaptosomes (5).…”
Section: Discussionmentioning
confidence: 99%
“…The implicated mechanisms behind the neuropathy have found to link with the increased oxidative stress leading to free radical damage to the nerves. 19,20 Besides, direct effects to the human body, alcohol intoxication is also associated with the social problems, including domestic violence, traffic accidents, child neglect, abuse, absenteeism in the workplace and others. 21 The harmful use of alcohol becomes the leading risk factor for death in male ages from 15-59 due to the injuries, violence and diseases.…”
Section: Discussionmentioning
confidence: 99%